Shedding the Light on Insurance Brokers”™ Remuneration: the Role of the Fees - Latorre Guillem, Miguel íngel (Opción, 2015)
The academic literature analyzed the way insurance brokers are compensated and different theoretical models, discussing the tradeoff between commissions and fees-based compensation system, have been developed. However, an ethical lens through which those systems are applied is still lacking in extant literature. To close this gap, in this manuscript we concentrate on fees and propose to the fore some practical examples brokers and customers may face. These examples, set in the Spanish market (which allows both commissions and fees), are used to discuss the role of fees in contexts where unethical behaviors may occur.Â